How to develop a focused research question for a rapid evidence review (Journal of EAHIL, 2023)
Rapid reviews are emerging as an alternative to systematic reviews, and they are now widely used to inform decision-making in healthcare. During COVID-19 pandemic, rapid reviews became more widespread. Some teams prepare reviews in a matter of days, instead of several weeks using streamlined systematic review methods. There are multiple roles for librarians within the evidence review process. As an expert searcher, the librarian must interact with the researchers, clinicians, and decision makers. A well-defined research question needs extreme specificity and preciseness which guides rest of the review.  Developing a focused question   workshop provided an overview of rapid review methods. Discussion and activities on developing a focused research question. How to start with broad topic and narrow it down to a question that is clear, relevant and answerable.